2017
DOI: 10.4081/ija.2016.795
|View full text |Cite
|
Sign up to set email alerts
|

Yield, quality and water use efficiency of processing tomatoes produced under different irrigation regimes in Mediterranean environment

Abstract: Marketable yield is the main objective in tomato production, but fair values for quality parameters are also becoming very important. A research project was undertaken for two years to assess the impact of water-saving techniques on yield, fruit quality and water use efficiency (WUE) of processing tomato (cv. Pullrex) in the Mediterranean environment. Additionally, to better understand how irrigation may affect tomato traits, different statistical techniques were applied to the results. Total yield was reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…High marketable yield is the most important goal in processing tomato production [41]; however, a large amount of external inputs is required [42]. Processing tomato sustainability may be increased by adopting the OFS [43] and recently consumers are increasing the purchase of organic farming products [44].…”
Section: Discussionmentioning
confidence: 99%
“…High marketable yield is the most important goal in processing tomato production [41]; however, a large amount of external inputs is required [42]. Processing tomato sustainability may be increased by adopting the OFS [43] and recently consumers are increasing the purchase of organic farming products [44].…”
Section: Discussionmentioning
confidence: 99%
“…In a dry (2015) and a mildly wet (2016) year, during the early fruit development (ST3) the air temperature was above 30 • C through many days but it remained below 30 • C in the dry year (2011) ( Figure 1). The unequal distribution of precipitation and high daily temperature, particularly during the fruit development and ripening stages, significantly affected the yield and quality [40].…”
Section: Climate During the Growthmentioning
confidence: 99%
“…Data obtained in a study at Foggia in Apulia [30] indicated that farmers tend to over irrigate tomato crops, with no significant increase in the marketable fruit yield and quality, as reported in other research [20]. Moreover, the same authors [30] indicated that the adoption of variable irrigation regimes as RDI restoration of 60%, 80%, and 60% of the maximum ETc during the three main tomato phenological stages (i.e., from plant establishment to flowering of the first truss, from flowering of the first truss to fruit breaking colors of the first truss, and from fruit breaking colors of the first truss to harvest), was effective to save water, as shown by other authors [31,34] at Viterbo (Latium) and Lavello (Basilicata). A study at Matera in Basilicata [32] indicated that water restoration of 50, 75, and 100% of crop evapotranspiration showed no statistical differences among the irrigation volumes in relation to tomato yield and quality.…”
Section: Discussionmentioning
confidence: 58%
“…A field research was carried out in 2011 in Foggia province (41 • [31]. MAT and MAP were 14.5 • C and 518 mm, respectively.…”
Section: Apuliamentioning
confidence: 99%